24-hour ambulatory blood pressure monitoring in chronic kidney disease and its influence on treatment - Cunha,Catia (2017)
Introduction: Chronic kidney disease (CKD) is strongly associated with hypertension (HTN) and each can cause or aggravate the other. Misclassification of BP control is an important problem in hypertensive patients with CKD, making ambulatory blood pressure monitoring (ABPM) an important tool. The aim of our study was to review the influence of ABPM results in antihypertensive treatment and BP control in hypertensive CKD patients. Methods: Retrospective observational study; inclusion of hypertensive CKD patients stages 1 to 5 not on dialysis who performed ABPM in our department; data collected from clinical records and ABPM reports. Results: A total of 54 hypertensive CKD patients were reviewed. Reasons appointed for requesting ABPM included suspicion of resistant hypertension (40.7%), uncontrolled hypertension (29.6%), white coat hypertension (16.7%), hypotension (9.2%) and masked hypertension (3.8%). Interestingly, pre-ABPM clinical interpretation of BP control was found inadequate in 55.6% of patients. Conclusion: Misclassification of BP was a significant problem. As a result of these findings our department incorporated ABPM more routinely as recommended best practice